2000
DOI: 10.1046/j.1365-2141.2000.01834.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular accumulation of factor VIII induced by missense mutations Arg593→Cys and Asn618→Ser explains cross‐reacting material‐reduced haemophilia A

Abstract: Summary. Patients with cross-reacting material (CRM)-reduced haemophilia A exhibit reduced levels of factor VIII antigen. In this study, we determined the molecular basis of the genetic defect in the factor VIII gene induced by either the Arg 593 !Cys or the Asn 618 !Ser missense mutation, identi®ed in two CRM-reduced haemophilia A patients. We introduced either the Arg 593 !Cys or the Asn 618 !Ser mutation into a B-domain-deleted factor VIII cDNA and expressed the modi®ed cDNAs in C127 cells. Reduced levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…The ROS produced as a consequence of FVIII misfolding may exacerbate inflammatory responses, as well as stimulate production of anti-FVIII antibodies. We have shown that BHA feeding prevents apoptosis, suppresses ER stress, and increases the secretion of FVIII delivered by adenovirus, as well as a folding-defective functional FVIII mutant R593C that is known to cause hemophilia A (27). Therefore, antioxidants may provide a useful adjuvant to improve FVIII production in patients who receive gene therapy or who have mutations that disrupt FVIII folding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ROS produced as a consequence of FVIII misfolding may exacerbate inflammatory responses, as well as stimulate production of anti-FVIII antibodies. We have shown that BHA feeding prevents apoptosis, suppresses ER stress, and increases the secretion of FVIII delivered by adenovirus, as well as a folding-defective functional FVIII mutant R593C that is known to cause hemophilia A (27). Therefore, antioxidants may provide a useful adjuvant to improve FVIII production in patients who receive gene therapy or who have mutations that disrupt FVIII folding.…”
Section: Discussionmentioning
confidence: 99%
“…The expression vectors for wtFVIII, BDD, and 226/N6 were previously described (20). Vectors for FVIII-BDD and R593C-BDD were kindly provided by J. Voorberg (Amsterdam, The Netherlands) (27). Plasmid DNA samples (100 g) were diluted in 2.5 ml lactated Ringer buffer and infused over 10 sec into the tail vein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the haemophilia A mutation database, patients with Arg593Cys had similar FVIII antigen and activities levels pointing towards poor secretion of a functional protein. In addition, Roelse et al using a heterologous expression system found that an Arg593Cys substitution led to elevated accumulation of intracellular functional FVIII relative to wildtype FVIII [9]. The patient with the Arg593Cys had a polyclonal response that cleared both endogenous and exogenous FVIII.…”
Section: Discussionmentioning
confidence: 99%
“…16 In addition, Roelse et al found that R593C and N618S A2-domain substitutions led to elevated accumulation of intracellular functional fVIII relative to wt-fVIII. 33 In these studies, the kinetic block in fVIII synthesis was not identified.In the present study, we used conformation-specific MAbs, which have been used as tools to study protein folding, including intracellular folding intermediates, 34 to detect folding intermediates in the biosynthesis of wt-fVIII and N1922S-fVIII. An intermediate containing incompletely folded A3 and C1 domains was identified after measurement of the apparent ratios of intracellular to secreted N1922S-fVIII ( Figure 6C).…”
mentioning
confidence: 95%